Versatilidade de compostos a base de nióbio: aplicação em oxidação de glicerina residual, em terapia fotodinâmica e formação de nanogéis - Poliane Chagas (2019)
The objective of this work was to produce reactive oxygen species fromniobium polyoxe obtained from the reaction of commercial niobium oxides and hydrogen peroxide. Hydrogen peroxide promotes the leaching of oligomeric species of niobium with high negative charge and high niobium content. These species were used as a source of niobium in the impregnation of catalysts, since most of the salts are of low solubility, providing low amount of niobium in the impregnation processes. The catalysts were obtained by the impregnation of a synthetic silica with the niobium polyoxe, PxNb@SiO2. The bifunctional (acid and oxidant) character of the materials produced with niobium provided high conversion (above 90% after 8h in continuous flow) in the reactions withresidual glycerin of the biodiesel production and good selectivity for formic acid. Furthermore, the niobium polyoxe can directly oxidize molecules or tumor cell by transfer the reactive oxygen species from (PxNb_liq). Niobium polyoxe was used in the oxidation of carcinogenic cell species (K562, HeLa and MRC-5) where it was shown to be capable of transferring reactive oxygen species preferentially killing diseased cells (for HeLa cells the pure material, PxNb_líq, in concentrations above 5 ppm, had a cell viability of less than 4%; for the healthy cell, MRC-5, the viability at the same concentration is about 40%). The high negative charge of the niobium polyoxe allowed to obtain nanogels by the addition of cations that neutralized the loads promoting the formation of stable structures capable of storing micro / macronutrients (cations) of the soil and water. The results showed a high accumulation of Zn2+ (approximately 30 mg L-1) and water, presenting a nanogel capable ofaccumulating and releasing moisture and nutrients to the soil.